Moderating effect of risk management committee on the relationship between financial risk and profitability of listed insurance companies in Nigeria - Fali, Ibrahim Mallam; Ahakiri, Francis Idiege; Inah, Egu Usang; Oyong, Ogar-Abang John; Banku, Mbu-Ogar, Geraldine; Ochi, Inyang, Inyang; Gabriel, Emori, Enya; Ogenyi, Oboh John; Gbenga, Lawal Suleiman; Imong, Nelly Raphael; et al. (Edelweiss Applied Science and Technology, 2025)
This study investigates the moderating effect of the Risk Management Committee (RMC) on the relationship between financial risk and profitability of listed insurance companies in Nigeria, addressing previous mixed findings in the literature. The population comprises 23 listed insurance companies, with a sample of 15 firms selected. Secondary data from 2012 to 2021 were sourced from annual financial reports. Guided by the positivist paradigm, the study adopted a causal research design and employed panel data analysis using fixed effects regression estimation. Results show that the RMC significantly moderates the relationship between liquidity risk and profitability, as well as between technical provision risk and profitability. No significant moderating effects were observed for credit risk, reinsurance risk, solvency risk, or underwriting risk. The presence of the RMC reduces liquidity risk and enhances profitability, while its interaction with technical provision risk has a negative and significant influence on profitability. A competent RMC can mitigate liquidity risk and boost profitability but may also intensify the adverse effects of technical provision risk. Insurance firms should strengthen financial risk controls and ensure RMC members possess the technical expertise needed to manage diverse risks effectively.